2020
DOI: 10.1021/acsnano.0c02047
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Nickel Iron Hexacyanoferrate as Ultra-Long-Life Cathode Material for Potassium-Ion Batteries with High Energy Density

Abstract: The abundant reserve and low price of potassium resources promote K-ion batteries (KIBs) becoming a promising alternative to Li-ion batteries, while the large ionic radius of K-ions creates a formidable challenge for developing suitable electrodes. Here Ni-substituted Prussian blue analogues (PBAs) are investigated comprehensively as cathodes for KIBs. The synthesized K1.90Ni0.5Fe0.5­[Fe­(CN)6]0.89·0.42H2O (KNFHCF-1/2) takes advantage of the merits of high capacity from electrochemically active Fe-ions, outsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 71 publications
1
103
0
Order By: Relevance
“…Thenon-stoichiometric proportion of Ni and Fe could be attributed to the formation of [Fe(CN) 6 ] 4À vacancies during the co-precipitation process. [26] Thec rystallographic information of KNiHCF was analyzed by Rietveld refinement (Figure 1a), and detailed refinement results are listed in the Supporting Information, Table S2. TheKNiHCF shows acubic phase with F " 43m(216) space group (a = b = c = 10.0443 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thenon-stoichiometric proportion of Ni and Fe could be attributed to the formation of [Fe(CN) 6 ] 4À vacancies during the co-precipitation process. [26] Thec rystallographic information of KNiHCF was analyzed by Rietveld refinement (Figure 1a), and detailed refinement results are listed in the Supporting Information, Table S2. TheKNiHCF shows acubic phase with F " 43m(216) space group (a = b = c = 10.0443 ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that pushing the doping percentage higher to 8 wt% is harmful to the electrochemical performance of PBAs and leads to serious capacity degradation. Chong et al [ 103 ] also confirmed the electrochemical performance of PBAs can be significantly improved when half of Fe was replaced by Ni. As shown in Figure 7g,i, the Ni‐substituted KFHCF, K 1.9 Ni 0.5 Fe 0.5 [Fe(CN) 6 ] 0.89 ·0.42H 2 O, demonstrates improved rate capability (53.4 mA h g −1 at 0.5 A g −1 ) and enhanced cycling stability (82.3% after 1000 cycles), compared with the pristine KFHCF and other PBA cathode materials (Table 1).…”
Section: Improvement Strategies To Endow Pbas As High‐performance Catmentioning
confidence: 92%
“…[9][10][11] Therefore, an increasing focus on sodium and potassium ion batteries has emerged rapidly. [12][13][14][15] Nevertheless, the large ionic radius is always a big challenge to find suitable host materials. Meanwhile, the use of organic electrolyte will bring about many safe and environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, future growth and prospect of LIBs would be hampered to some extent by reason of the maldistribution of lithium, high cost and safety concern [9–11] . Therefore, an increasing focus on sodium and potassium ion batteries has emerged rapidly [12–15] . Nevertheless, the large ionic radius is always a big challenge to find suitable host materials.…”
Section: Introductionmentioning
confidence: 99%